Understanding the complexity of provincial-level elite sport policy change: The case of Shanghai municipality - Ma, Yang (Frontiers in Psychology, 2022)
The analysis of elite sport policy changes at the provincial level remains relatively uncharted territory despite the substantial contributions of provincial level elite sport to national elite sport success. Data were gathered from semistructured face-to-face interviews and official and semiofficial documents. The key findings were that (1) Guangdong, as a provincial compatriot of Shanghai, has made tremendous efforts and obtained notable achievements in professional football and thus serves as a powerful stimulant for policy reform regarding elite sports in Shanghai; (2) the policy stream has been strengthened by knowledge-based (epistemic) communities at the Shanghai University of Sports that can examine cause and effect relationships and further propose specific policies; and (3) the general director of the Shanghai Administration of Sports plays a central role in advocating for policy proposals. The current research offers practical insights into strategies for reviewing policy trajectories to enhance policy design and implementation.